Transdisciplinarity for Transformation : Responding to Societal Challenges through Multi-actor, Reflexive Practices - Regeer, Barbara J. HerausgeberIn; Klaassen, Pim HerausgeberIn; Broerse, Jacqueline E. W. HerausgeberIn (Springer Nature, 2024)
This open access book presents state-of-the-art insights on transdisciplinary work towards societal transformation. It provides theoretical and practical guidance and tools, applicable across diverse empirical settings. The book supports researchers and practitioners, especially those early in their careers, to navigate dilemmas inherent in transdisciplinarity for transformation. The book serves as a valuable resource for (graduate) educational programs in any field open to transformation-oriented transdisciplinary collaboration. It comprises three sections: Design & Evaluation; Diversity & Inclusion; Roles & Competences. Each section includes a chapter on theoretical advancements, multiple empirical chapters presenting insights from various fields and contexts, and practical guidance conducive to engaging in high-quality, just and equitable transdisciplinary processes directed at sustainable transformation